Short-term starvation and refeeding in the greater amberjack (Seriola dumerili, Risso 1810): New insights on physiological and metabolic traits - Anyell Caderno; Paula Simó-Mirabet; Miguel García-Zara; Juan Antonio Martos-Sitcha (Aquaculture Reports)
The greater amberjack (Seriola dumerili) is a fish species with high commercial value and excellent growth rates, which has led to increasing interest in the aquaculture sector to optimize and expand its production. To gain a deeper insight into its physiological aspects, the present study aimed to evaluate the metabolic responses of S. dumerili juveniles after a short period of starvation and subsequent refeeding. For this purpose, the fish were fed ad libitum twice a day for four weeks and were then subjected to a starvation challenge followed by a refeeding period of seven days each. After one week of starvation, the fish showed weight loss but were able to adapt their metabolism by maintaining carbohydrate levels and using lipids and proteins as the main energy sources. All this was supported by decreased glycogenolytic potential during starvation, indicated by lower GP activity, and an increase in gluconeogenic pathway, as evidenced by the observed activity of FBP, LDH, and transaminases (ALT and AST). Moreover, the refeeding period stimulated growth processes by activating metabolic pathways, resulting in higher feed efficiency rates. Correspondingly, the highest plasma cortisol levels were observed during the refeeding period, stimulating anticipatory activity after starvation and contributing to metabolic recovery. In conclusion, S. dumerili can efficiently regulate its internal environment during a short period of starvation, improving feed efficiency and growth parameters after refeeding and rapidly restoring the initial metabolic state. These results could represent promising insights to enhance the feeding program for this species.